Antioxidant Properties of 5-ASA: Potential Mechanism for Its Anti-Inflammatory Activity - T Yamada; C Volkmer; MB Grisham (Canadian Journal of Gastroenterology)
There is a growing body of experimental data to suggest that the inflamed intestine and/or colon may be subjected to considerable oxidative stress. The most probable source of these oxidants are the phagocytic leukocytes, since these cells are present in large numbers in the inflamed mucosa and are known to produce significant amounts of potentially injurious reactive oxygen species in response to inflammatory stimuli. The authors' laboratory and others have demonstrated that 5-aminosalicylic acid (5-ASA) possesses potent antioxidant activity, including free radical scavenging properties and the ability to decompose neutrophilic oxidants (eg, hypochlorous acid) and detoxify hemoprotein-associated oxidizing agents. 5-ASA has the additional property of being able to chelate iron and render it poorly redox active. Therefore, it is proposed that much of the anti-inflammatory activity of 5-ASA may be due to its numerous antioxidant properties.